The differentiated countryside - Murdoch, Jonathan (Routledge studies in human geography, 2003)
Using an innovative theoretical approach based on 'networks of conventions', the book investigates the 'regionalisation' of the English countryside through case studies of the 'preserved', the 'contested' and the 'paternalistic' countryside.